THE REALITY OF MATERNAL AND CHILD HEALTH IN LIGHT OF ACHIEVING THE OBJECTIVES OF GOAL 3 OF THE 2030 SUSTAINABLE DEVELOPMENT AGENDA – ALGERIA AS A MODEL (Lex localis - Journal of Local Self-Government, 2025)
This article aims to shed light on the state of maternal and child health in Algeria by conducting a statistical observation of the maternal mortality variable and the under-five child mortality variable. It follows the evolution of their indicators and assesses the extent to which Algeria has achieved the first and second targets of Goal 3 in the 2030 Sustainable Development Agenda. Statistics have shown that Algeria succeeded in achieving the target of reducing the maternal mortality ratio to less than 70 per 100,000 live births by the year 2013, despite the existing shortcomings on the ground, which the state continues to address and improve. Algeria has also, albeit at a slow pace, managed to achieve the goal of reducing the stillbirth rate to less than 12 per 1,000 births by 2023, as well as reducing the under-five child mortality rate to below 25 per 1,000 live births by 2019.